2008
DOI: 10.1111/j.1468-3148.2008.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Measures of Job Performance for Support Staff in Housing Services for People with Intellectual Disabilities

Abstract: Background There is an absence of research concerning the assessment of housing support worker job performance, particularly in the development of job performance measures that reflect the priorities of people with intellectual disabilities and their families. Method A worker-oriented job analysis method was used to develop four short job performance measures for direct housing support staff, from the perspective of people with intellectual disabilities (n = 82), family members (n = 38), support staff (n = 122… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 15 publications
6
19
1
1
Order By: Relevance
“…The findings of this research are consistent with the previous research of Clarkson et al (2009) whose findings related to workers in forensic services for people with ID, FIELD (2006) whose findings related in general to disability workers and Hatton et al (2009) whose findings relate to RDCWs specifically. interacts with people, kind-natured, fun, helpful, respectful) and the practical skills and knowledge of RDCWs (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The findings of this research are consistent with the previous research of Clarkson et al (2009) whose findings related to workers in forensic services for people with ID, FIELD (2006) whose findings related in general to disability workers and Hatton et al (2009) whose findings relate to RDCWs specifically. interacts with people, kind-natured, fun, helpful, respectful) and the practical skills and knowledge of RDCWs (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…This study supported findings of previous research that has indicated that residents place a stronger emphasis on the interpersonal behaviours of RDCWs whereas managers place more emphasis on the skills and knowledge of RDCWs (FIELD 2006;Clarkson et al 2009;Hatton et al 2009). This study supported findings of previous research that has indicated that residents place a stronger emphasis on the interpersonal behaviours of RDCWs whereas managers place more emphasis on the skills and knowledge of RDCWs (FIELD 2006;Clarkson et al 2009;Hatton et al 2009).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations